Activities of Medical Educational Development Center from the Views of the Faculty Members of Kerman Medical Sciences University - Zahra Jalili; Esmat Nouhi; Ali Malekzadeh (Kerman University of Medical Sciences, 2004)
Background: The necessity of improving academic and higher education quality particularly in Medical Sciences Universities and increasing the efficiency of Health care and Remedy programs are obvious Medical Educational Development Centers try to achieve their goals in the areas of curriculum planning teacher training continuing education evaluation and research in education Objective: The aim of this study was to investigate the views of the faculty members of Kerman Medical Sciences University about the activities of Medical Educational development center Methods: This crosssectional study carried out in 2003 The sample consisted of the faculty members of Kerman Medical Sciences University (N=307) of which about half (n=145) were selected by simple random sampling Data were gathered through a researcher - made questionnaire that rated by experts for validity and computed internal consistency reliability with cronbach alpha coefficient of (r=079) Results: According to the results the most accepted activities of the center were "Designing and carrying out clinical skills educational programs for medical students" (966%) "active participation in the revision of medical educational programs" (931%) "cooperation with educational departments in designing lesson plans based on new materials and resources" and "Holding educational workshops for the familiarization of the faculty members with new medical softwares and their applications" (each 924%) While the least accepted activities were providing "facility for lectures" "access to resources gathering and symposiums on medical education" and "taking advantage of the experienced instructors in designing programs for the center" (each 614%) "participation in the evaluation of research projects and dissertations" and "helping the medical society to have a better understanding of the changing medical needs of the community" (each 67%) In whole by obtaining 787% of the total score the faculty members showed a relatively positive view towards current activities of the center From all subjects 875% showed tendency for participating in the activities of the center Conclusion: The positive view of the faculty members towards current activities of the center is a turning point in further expansion of the center and establishing the same units in all colleges to improve medical education goals